Comparative analysis of the expression of subject-predicate relations in Ukrainian and Russian languages - Тростинська, О.; Тарлєва, А. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
A special functional and communicative language linguodidactic model that considers syntax as a key system being organized all the other language levels in modern linguistics. Structural and semantic core of a sentence as a communicative unit formed by the subject-predicate relations: to study the paradigm and regular realizations of these relationships is an important task of language training for foreigners. It is important to describe enough amount of block diagrams (samples) of simple sentences for communicative purposes when teaching Russian and Ukrainian as foreign languages and identify the main differences between grammatical subject-predicate relations of two languages. Semantically equivalent structures can be expressed in different language forms. However, using the same structural expression can convey entirely different meanings. We understand the subject as a person (or thing) which produces the action, experiences the condition or it is the carrier of a certain feature. Grammatically it is expressed by a nominative subject in contrast to the logical one. Ways of expressing the logical subject in Ukrainian and Russian languages are the same. If the subject of the sentence is not active, its actions are unconscious, its state is uncontrollable, it can be expressed in the sentence by forms of indirect cases. In this case, linguists talk about lowering the rank of the subject. Predicate has also the common forms of expression in Ukrainian and Russian languages. Primarily it is a verb in different grammatical forms. Unlike the Russian language in Ukrainian a short form of the adjective is used only in the singular masculine nominative and accusative case and acts as the definition in the sentence. Adjectives of full penalties structure play the role of predicate in Ukrainian language. Passive language turns in the instrumental case of the acting person are not peculiar to the modern Ukrainian language. Passive phrases are less used in Ukrainian language that’s why we might predict that Ukrainian mentality is characterized by a great responsibility for the world around and the place of a human being in this world. The difference in the forms of expressing subjects and predicates in Russian and Ukrainian languages should be taken into account when working-out textbooks in Ukrainian as a foreign language.